COLLEGE EDUCATION AS A REQUIREMENT FOR CERTIFIED PUBLIC ACCOUNTANTS—THE NEW YORK EXPERIENCE. - Webster, Norman E. (The Accounting Review, 1946)
Abstract The article presents a discussion on the topic, College Education As a Requirement for Certified Public Accountants, The New York Experience. This is the second time that the author has been invited to present a study related to the topic. He discusses the result of the examination of 180 candidates from fifteen schools in several states of the U.S. and of ten times as many from New York State schools. This convinces the author, that students who have spent four years in the day classes or six years in the evening classes in the schools have been exposed to a quantity and quality of instruction which should have prepared them for the examinations in Commercial Law, Theory of Accounts, and the theoretical parts of auditing. The author does not believe, that schools were or could be prepared to teach successfully the subject of Practical Accounting or the practical part of auditing. A high school diploma does not insure that the holder has satisfactorily completed a four year course in that school.